Great cases of Scotland Yard - Reader's Digest Association (Pleasantville, N.Y. : Reader's Digest Association, 1978)
Egleton, C. The stealing of Muriel McKay.--Jenkins, E. Neill Cream, poisoner.--Garve A. The case of Stanley Setty.--Graham, W. The Wembley job.--Kennedy, L. The Portland spy case.--Williams, E. Doctor Crippen's diary.--Braddon, R. The Shepherd's Bush case.--Symons, J. The siege of Sidney Street.
Egleton, C. The stealing of Muriel McKay.--Jenkins, E. Neill Cream, poisoner.--Garve A. The case of Stanley Setty.--Graham, W. The Wembley job.--Kennedy, L. The Portland spy case.--Williams, E. Doctor Crippen's diary.--Braddon, R. The Shepherd's Bush case.--Symons, J. The siege of Sidney Street.
Keywords: Great Britain. -- Metropolitan Police Office. -- Criminal Investigation Dept; Crime -- Great Britain -- Case studies; Criminal investigation -- Great Britain -- Case studies